Au‐assisted growth of InAs nanowires on GaAs(111)B, GaAs(100), InP(111)B, InP(100) by MOVPE. Issue 5 (19th March 2013) - Murakami, S.; Funayama, H.; Shimomura, K.; Waho, T.; Krishna, Sanjay; Plis, Elena
Abstract Au‐assisted growth of InAs NWs by MOVPE growth was investigated. We will discuss the NWs characteristics on GaAs and InP substrate with (111)B and (100) orientation, and on the V/III ratio during the growth. We have observed the growth direction of NWs on each substrates and confirmed that the surface diffusion have relation to the diameter of NWs. In the GaAs (111)B substrate, the diameter and length of NWs were depended on the local density of NWs. Furthermore, the tapered NWs were decreased by lowering the V/III ratio. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)